2020
DOI: 10.1016/j.ijso.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and associated factors of post-operative pain after emergency Orthopedic surgery: A multi-centered prospective observational cohort study

Abstract: Introduction: Emergency orthopedic surgeries are performed on a daily and night basis across the world and, different levels of postoperative pain is commonly reported early and late in the postoperative period. Despite the availability of evidence-based international reports, still it is not clearly stated in Ethiopia. Objective: To determine the incidence and associated factors of post operative pain after Emergency Orthopedics Surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…This is likely due to the advantage of nerve block anesthesia for postoperative pain management. Several other studies done in Ethiopia [ 12 , 18 ], Tanzania [ 19 ], Brazil [ 34 ], and France [ 35 ] reported the same phenomenon, indicating that patients who had general anesthesia had a higher intensity of postoperative pain when compared to regional anesthesia. Moreover, a clinical practice guideline strongly acknowledged clinicians to consider local or regional block anesthesia during operative fixation of fractures and as part of postoperative multimodal pain management [ 36 ].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This is likely due to the advantage of nerve block anesthesia for postoperative pain management. Several other studies done in Ethiopia [ 12 , 18 ], Tanzania [ 19 ], Brazil [ 34 ], and France [ 35 ] reported the same phenomenon, indicating that patients who had general anesthesia had a higher intensity of postoperative pain when compared to regional anesthesia. Moreover, a clinical practice guideline strongly acknowledged clinicians to consider local or regional block anesthesia during operative fixation of fractures and as part of postoperative multimodal pain management [ 36 ].…”
Section: Discussionmentioning
confidence: 60%
“…In a meta-analysis that mainly included studies from Western countries, the following preoperative predictors for poor acute postoperative pain control in multiple surgical specialties were identified: pain catastrophizing [ 15 ], younger age, female sex, smoking, presence of preoperative pain, history of anxiety and depressive symptoms, sleep difficulties, and higher body mass index [ 16 ]. Similarly, in studies of a variety of surgeries in developing countries including Ethiopia, previous surgery [ 13 ], lower educational status [ 11 ], younger age [ 11 , 17 ], female sex [ 17 ], longer duration of surgery [ 9 , 13 ], presence of preoperative pain and anxiety [ 13 , 18 ], general anesthesia, peripheral nerve block [ 12 , 18 , 19 ] were identified as risk factors for moderate to severe pain.…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate analyses showed this had an odds ratio of 2.50 for experiencing a return to the operating room. Studies have reported associations of emergency patients with postoperative complications related to pain, respiratory, and wound issues [ 21 , 22 ]. Additional information is needed to explain the increased risk of poor health outcomes related to emergency status which may be caused by referred admission on non-trauma emergency surgical cases and surgical delays [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sociodemographic variables and severity of preoperative pain were comparable between groups as shown in (Table1). The median and IQR of preoperative pain through the numerical rating scale (NRS) at rest were 3 (2-4) and 2 (1-4) between 3IN1 and FICB, respectively, while preoperative pain through the numerical rating scale (NRS) at movement was 5 (5-6) and 5 [3][4][5][6][7] between 3IN1 and FICB, respectively, as shown in (Table 1). In this study, the most practiced surgical treatment of femoral fracture was intramedullary nailing which accounts for 69%, and 56% of three-in-one-block and fascia iliaca blocks, respectively (Table 2).…”
Section: Socio-demographic Variablesmentioning
confidence: 96%
“…A road traffic accident is the most common cause of fracture, and the femoral bone fracture was the predominant [1]. Orthopedic surgery is associated with severe acute pain and persistent chronic pain with an incidence of 70.5% in the study area [2], [3], which shows pain associated with postoperative orthopedic surgery is not treated adequately. Practicing a better pain management strategy is one of the most common postoperative cares in orthopedics surgical procedures, and untreated pain results in inability to do physiotherapy, stiffens of joint immobility [4,5], delayed wound healing, hemodynamic disturbance, transition to chronic pain [6], increased financial costs, prolonged hospital stay, increased morbidity and mortality risks [7].…”
Section: Introductionmentioning
confidence: 98%